Decision Support System For Determining Exemplary Students Using SAW Method - Sudradjat, Adjat; Destiana, Henny; Sefenizka, Aprilah Amira (Sinkron : jurnal dan penelitian teknik informatika, 2020)
In order to motivate students to continue to excel, MTs Al Falah undertakes activities to develop students' potential through determining exemplary students. However, the decision to determine exemplary students is not based on academic and non-academic abilities, but on the subjectivity of the principal and teachers. So that many complain about the decision of the selection of exemplary students who are not well targeted or deserve to be exemplary students. There is no information system that supports the determination of exemplary students on MTs Al Falah, It is less precise in determining the exemplary students on MTs Al Falah, decision support systems in Determination of the Exemplary Students using the Simple Additive Weighting (SAW) method is based on 5 criteria, namely the value of knowledge, the value of skills, class rank, extracurricular activity, extracurricular values. The results obtained will be in the form of exemplary student rankings. Then the student who gets the highest score in five categories with a percentage of 0.97 is Afifah Angelia Azhariyanti. The Simple Additive Weight method can help the school especially in determining a number of issues regarding education, one of which is to determine exemplary students. Because this method is a weighted method of rating the performance of each alternative.